РОЛЬ СОЦИАЛЬНО-ЭНОМОМИЧЕСКОГО РОСТА МАЛОГО БИЗНЕСА И ЧАСТНОГО ПРЕДПРИНИМАТЕЛЬСТВА РЕСПУБЛИКИ УЗБЕКИСТАН - Хожалепесов, П.З.; Калимбетова, А. (SCIENCE and SOCIETY, 2022)
The article describes the current stage of economic reforms in Uzbekistan, the development of small business and private entrepreneurship, providing it with broad economic freedom. In this regard, special attention is paid to the development of small business and entrepreneurship in the country. Since this issue is considered as a strategic task of the economic policy of our state, currently, this sector is leading not only in accelerating economic growth, but also in solving the issues of employment and income growth that are extremely important for our country.